The Correlations Between Students’ Vocabulary Mastery And Speaking Skill To The Tenth Grade Students Of Smk Negeri 1 Angkola Timur - Nursaima Harahap (ETANIC Journal Of English Language Teaching And Applied Linguistics, 2023)
The background of the problem in this research was aimed at finding out the correlation between vocabulary mastery and speaking skill of the tenth-grade students of SMA Negeri 1 Angkola Timur. The population of this research of the tenth-grade students of SMA Negeri 1 Angkola Timur. The members of population were 90 students. The 90 students were taken by a researcher using Cluster Random Sampling as the class sample. The hypothesis in this research was there is a significant correlation between vocabulary mastery and speaking ability of the tenth-grade students of SMA Negeri 1 Angkola Timur. In collecting the data, the researcher used the multiple-choice test to measure vocabulary mastery and oral test to measure speaking ability. In analyzing the data, the researcher used the Pearson Product Moment formula. After analyzing the data, it was found that r calculated was .84 with level significance .04, and the degree of freedom (df= n-2) was 28. It means that r- counted was higher than r-table (.83>.32). So, the relationship between two variables above was significant. Therefore, the alternative hypothesis, that said “There is significant correlation between vocabulary mastery and speaking ability of the tenth-grade students of SMA Negeri 1 Angkola Timur” was accepted. Based on the finding of this research, it could be concluded that there is correlation between vocabulary mastery and speaking ability of the tenth-grade students of SMA Negeri 1 Angkola Timur. It means that the students’ vocabulary mastery will improve students’ speaking skill.